MAIN EFFECTS OF USING TRADITIONAL METHODS AND INFORMATION TECHNOLOGIES IN HISTORY LESSONS (Conference Zone, 2022)
The article scientifically analyzes the advantages of using traditional methods and information technologies in history lessons. The state of modern education is such that the educational process is carried out in the conditions of a constant increase in the flow of information that needs to be mastered, which leads to an overload of educational programs. In such conditions, the quality of education depends on the correct performance of educational work, professional skills and qualifications of the teacher. Computer technologies have taken a strong place in the organization of the educational process in various subjects. The necessity and effectiveness of their use today is beyond doubt.